Spectral power graph of generalized quaternion groups - Romdhini, M.U.; Nawawi, A.; Al-Sharqi, F.; Al-Quran, A. (Asia Pacific Academic, 2024)
This paper examines the spectral properties of the power graph of the generalized quaternion group. We focus on the characteristic polynomial of the graph associated with adjacency, Laplacian, and signless Laplacian matrices. © 2024 Asia Pacific Journal of Mathematics.